Central nervous system depressant, analgesic and antidiarrheal effects of the seed extracts of Dimocarpus longan lour in rats - Ripa, Farhana Alam; Ibn Morshed, Mahmud Tareq; Afsana-Al-Sharmin; Papon, Shahed Bulbul; Islam, Md Rafiqul; Sheikh, Zara (© 2014 Tropical Journal of Pharmaceutical Research, 2016)
This article was published in Tropical Journal of Pharmaceutical Research [© 2014 Tropical Journal of Pharmaceutical Research] and the definite version is available at: http://www.ajol.info/index.php/tjpr/article/view/101488/90672